The flow fields generated by stationary and travelling downbursts and resultant wind load effects on transmission line structural system - Wu, Zhonghui; Iida, Yumi; Uematsu, Yasushi (Journal of wind engineering and industrial aerodynamics, 2021)
In many non-cyclone areas around the world, severe thunderstorm downbursts can produce annual gust peaks that are the design wind speeds of general structures, and the resultant wind loads pose a major potential threat to critical infrastructure, such as transmission line structural system. The flow fields generated by downbursts are different from those by the synoptic winds in the atmospheric boundary layer. In order to obtain a wind load model of downburst, scholars have made many attempts to study the flow characteristics of downburst-like events. However, in previous studies, the effects of different experimental setup parameters on distribution of downburst wind speed have not been fully discussed. In this paper, an experimental study is conducted using a pulsed wall jet experimental simulator located at Tohoku University, Japan, to analyse the flow fields of stationary and travelling downbursts, and the resultant wind load effects on transmission line structural system. The comparison results show that different experimental settings will affect the maximum wind speed obtained and the height providing the maximum wind speed. The translational speed ratio defined by the ratio of moving speed to jet inlet speed will affect the wind speed distribution in the longitudinal direction of the generated flow field of the travelling downburst. In addition, the comparative studies show that the wind speed distribution of travelling downburst cannot be simply expressed as the vector sum of stationary downburst wind speed distribution and the jet moving speed, and that speed of the travelling downburst can intensify the non-uniform wind loading relaying to the transmission line structural system. For the analysis of the downburst flow fields, a multi-degree-of-freedom analysis is needed to consider its three-dimensional effect, that is, the distributions of wind speeds along the three coordinate axes, and the comprehensive effects of influencing parameters. •Travelling speed can affect wind speed distribution of generated travelling downburst.•Wind speed distribution of travelling downburst cannot be simply expressed as vector sum of stationary downburst and jet moving speed.•Travelling speed can intensify non-uniform wind loading of travelling downburst relaying to transmission line structural system.•A multi-degree-of-freedom analysis is needed to consider three-dimensional effect of downburst wind fields.